The Nontitular Son of Man: A History and Critique - Burkett, Delbert (New Testament studies, 1994)
The expression ⋯ νἱ⋯σ το⋯ ⋯νθρώπον, found primarily in the Gospels on the lips of Jesus, has been the object of a centuries-long investigation that has sought to determine its meaning and origin. Patristic and medieval authors understood the phrase as a title of Jesus meaning ‘the Son of the human’, with ‘the human’ referring to either Mary or Adam. With the renewal of learning in the Renaissance and Reformation, interpreters began to examine the phrase in light of its Semitic background, tracing it to Hebrew ben adam or Aramaic bar enasha. A host of new interpretations arose. While most scholars continued to view the expression as some sort of title, others saw it as a nontitular idiom. Three possible idiomatic senses of the expression were investigated: the circumlocutional sense (‘this man’ = ‘I’), the generic sense (‘man’ in general), and the indefinite sense (‘a man’, someone). These nontitular interpretations, part of the debate since 1557, have become more prominent in the last 25 years and form an important feature of the current discussion.